STRENGTHENING ACADEMIC CULTURE IN URBAN MADRASAH ALIYAH: A MULTIPLE CASE STUDY BASED ON TOTAL QUALITY MANAGEMENT AT MADRASAH ALIYAH YOGYAKARTA - Haningsih, Sri; Budiwati, Anisah; Zainuddin, Nurkhamimi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2026)
The strengthening of academic culture in urban Madrasah Aliyah has become an urgent agenda amid increasing institutional competition, public accountability demands, and the transformation of Islamic secondary education in Indonesia. While numerous studies have addressed school quality improvement, limited research specifically examines how Total Quality Management (TQM) is systematically operationalized to construct a sustainable academic culture within urban madrasah settings. This study aims to explore and critically analyze the implementation of TQM principles in strengthening a sustainable academic culture across selected urban madrasah contexts. Using a qualitative multiple case study approach, data were collected through in-depth interviews with principals, teachers, and quality assurance teams, supported by classroom observation and institutional document analysis. The findings demonstrate that academic culture strengthening is not merely programmatic but structurally embedded through five interrelated dimensions: visionary leadership grounded in quality commitment, continuous improvement in pedagogical practices, data-driven evaluation systems, collaborative teamwork mechanisms, and integration of Islamic values with academic performance standards. The study argues that TQM in urban madrasah functions as a cultural transformation framework rather than a managerial tool alone. This research contributes to the development of Islamic education management by contextualizing TQM within the sociocultural dynamics of urban madrasah and offering an integrative model that bridges managerial efficiency with value-based educational orientation. The findings offer both conceptual refinement and practical implications for enhancing a competitive yet value-driven academic culture in Islamic secondary education institutions.